2021
DOI: 10.1155/2021/9670982
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Assessment of Natural Teeth Wear against Zirconia and Novel Glass-Fiber-Reinforced Composite Crowns in Primary Teeth by a Three-Dimensional Assessment Method

Abstract: Objectives. The main purpose of the study was to assess the material wear, antagonistic natural primary teeth wear, and microhardness of zirconia (ZR), a recently launched novel glass-fiber-reinforced composite crown (GFRC). The research question was, are these aesthetic crowns resulting in antagonistic natural primary tooth wear and the crown material itself? Methods. Forty-five primary canines were divided into three groups (15 per group) and mounted against Zr (Group A), GFRC (Group B), and natural teeth as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…By choosing materials with lower surface roughness, the dentist and the dental technician can reduce the risk of bacterial plaque retention and improve the long-term success of the dental treatments [ 10 , 13 , 21 , 30 ]. Additionally, it can facilitate proper maintenance and cleaning of dental materials to prevent the buildup of bacterial plaque [ 25 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By choosing materials with lower surface roughness, the dentist and the dental technician can reduce the risk of bacterial plaque retention and improve the long-term success of the dental treatments [ 10 , 13 , 21 , 30 ]. Additionally, it can facilitate proper maintenance and cleaning of dental materials to prevent the buildup of bacterial plaque [ 25 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, based on the maximum roughness threshold recommended by the previous research of Jones et al [29], the finishing protocols applied in our study would be considered clinically acceptable in terms of surface roughness, even though some differences were observed between the groups. By choosing materials with lower surface roughness, the dentist and the dental technician can reduce the risk of bacterial plaque retention and improve the long-term success of the dental treatments [10,13,21,30]. Additionally, it can facilitate proper maintenance and cleaning of dental materials to prevent the buildup of bacterial plaque [25,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as per manufacturer recommendations, the luting cement of choice for prefabricated zirconium crowns is bioactive resin-based glass ionomer cement which requires good gingival bleeding control prior to cementation. Numerous published studies have highlighted the success of resin-reinforced glass ionomers, 27 28 but a recent study conducted 29 concluded that packable conventional glass ionomer cement is more retentive than bioactive cement for the cementation of primary Zirconia crowns.…”
Section: Discussionmentioning
confidence: 99%
“…Fiberglass primary crowns, which are fabricated from fiber mesh sheets impeded in resin, were recently introduced. However, a recent randomized controlled study showed such crowns to have low wear resistance, colour deterioration, and poor gingival health with plaque retention [23].…”
Section: F I G U R E 3 Bar Chart Showing the Level Of Respondent Agre...mentioning
confidence: 99%